Incidence, predictors, and survival impact of acute kidney injury in patients with melanoma treated with immune checkpoint inhibitors: a 10-year single-institution analysis - Maen Abdelrahim; Omar Mamlouk; Heather Lin; Jamie Lin; Valda Page; Noha Abdel-Wahab; Joshua Swan; Umut Selamet; Cassian Yee; Adi Diab; Wadi Suki; Ala Abudayyeh (OncoImmunology, 2021)
Background: The incidence of renal immune-related adverse events (irAEs) is reported to be 3.8%, with varied definitions of acute kidney injury (AKI). This study reports a 10-year experience at MD Anderson Cancer Center of patients diagnosed with melanoma and treated with immune checkpoint inhibitors (ICIs) and evaluated the incidence of AKI, associated factors, and its association with overall survival. Methods: A retrospective chart review (2010–2019) of all patients with melanoma treated with ipilimumab, nivolumab, pembrolizumab, or atezolizumab was performed. All available serum creatinine data were extracted and used to calculate the estimated GFR (eGFR) using the CKD Epi equation, and to diagnose AKI using the two KDIGO (Kidney Disease: Improving Global Outcomes) criteria for defining stage I AKI in 1664 unique patients. Cumulative incidence rates of AKI after initiation of ICIs were calculated in the presence of death as a competing risk. The effects of covariates on the cumulative incidence function of AKI were evaluated in a univariant and multivariable analysis. Overall survival was estimated by Kaplan–Meier method in accordance to the occurrence of AKI. Results: The incidence of AKI by definitions 1a and 1b were 3.49% and 3.33%, respectively. After adjudication, AKI attributable to ICI was 58% and 65% of the overall incidence of AKI in each definition respectively. Increasing age was associated with decreased risk of AKI. Asian race was associated with a higher risk of AKI. Comorbidities were not associated with increased risk of AKI while use of proton pump inhibitors (PPI), ipilimumab or ICI combinations were significantly associated with AKI. AKI was not significantly associated with overall survival. Immune-related adverse events (irAEs) occurred in 30% of patients with AKI but their incidence was not different in patients with AKI attributable to ICI versus other AKI. Conclusions: In a large population of patients with melanoma treated with ICIs, an accurate documentation of AKI in setting of ICI use and predictors associated is presented. AKI following ICI use is infrequent, not associated with mortality, and associated with the use of ipilimumab, ICI combinations and PPIs.